Short Communication: Characterization of Rhizoctonia-like mycorrhizae associated with five Dendrobium species in Java, Indonesia - R Soelistijono; D.S. UTAMI; DARYANTI; M. FAIZIN; R. DIAN (Society for Indonesian Biodiversity, 2020)
Abstract. Soelistijono R, Utami DS, Daryanti, Faizin M, Dian R. 2020. Plankton biodiversity in various typologies of inundation in Paminggir swamp, South Kalimantan, Indonesia on dry season. Biodiversitas 21: 1007-1011. This study aims to determine the morphological and anatomical characteristics of Rhizoctonia-like mycorrhizae associated with the roots of five Dendrobium species; to determine the association between Rhizoctonia-like mycorrhizae with the root of five Dendrobium sp.; to obtain difference between Rhizoctonia-like mycorrhizae with the other in adjacent location Mycorrhizal observations of Rhizoctonia-like mycorrhizae in this study were carried out macroscopically (morphologically) and microscopically (anatomically). The macroscopic observation was performed by observing directly the development of fungal colonies on culture media. Microscopic observations were performed to determine the shape of the hyphal of fungi and the number of nuclei. The results showed that the Rhizoctonia-like mycorrhizae associated with the root of five species of Dendrobium sp. in Java were the binucleate Rhizoctonia groups (BNR). The binucleate Rhizoctonia has white colonies, right-angle branching hyphae, two nuclei, and brown hyphae. The association of the root of five species of Dendrobium sp.with Rhizoctonia-like mycorrhizae fungi was indicated by the existence of a peloton structure in cortical root tissue.